Humour in a holistic learning process of in a preschool setting. Unique soft toys and stories inspired and further developed by children’s sense of humour - Rönkkö Marja-Leena; Aerila Juli-Anna (Norway, 2022)
This study aims to examine the learning outcomes among preschool children of a holistic artsbased
learning process in which humour was the core theme. The study involved 17
preschoolers, who were given the task of working both collaboratively and individually and
designing a soft toy supported by a story that would make other people laugh. The results
suggested that humour and a variety of activities make an inspiring formula for holistic artsbased
learning. Humour, in the case of the children’s activities, meant creating incongruence
and surprise. The soft toys the children created were funny, well-meaning characters with
comical features. Children seemed to recognize the significance of cheering other people up;
in this respect, girls were more product-oriented than boys. Craft-making with the ingredient
of humour motivated the children and gave them story ideas. Additionally, the stories
highlighted the meaningfulness of the soft toys to the children. The collaborative phases of the
learning process helped children to come up with ideas for their story, as well as get feedback
on these ideas. The individual phases, on the other hand, gave the children enhanced
opportunities to express their own ideas.